Culturally-tailored cookbook for promoting positive dietary change among hypertensive Filipino Americans: a pilot study - Sijangga, Madelyn O.; Pack, David V.; Yokota, Nicole O.; Vien, Morgan H.; Dryland, Alexander D. G.; Ivey, Susan L. (Frontiers in Nutrition, 2023)
Among all Asian American subgroups, Filipino-Americans have consistently been shown to have the highest rates of hypertension, raising risks of heart attack and stroke. Despite this alarming fact, little has been done to investigate culturally-sensitive interventions to control hypertension rates in this vulnerable population. To address the lack of culturally-relevant lifestyle options for blood pressure management currently available to the Filipino community, this exploratory pilot study used a design thinking approach informed by culinary medicine to develop a culturally-tailored, heart-healthy, and low sodium recipe cookbook for Filipino Americans with hypertension and evaluate its feasibility as a hypertension intervention. Our team developed a cookbook using participatory methods and design thinking, utilizing input from five Filipino culinary experts and a Registered Dietitian. The cookbook incorporates traditional Filipino recipes, excerpts from community members’ interviews, and nutrient analyses. Twenty Filipinx-identifying individuals* who self-reported physician-diagnosed hypertension were recruited from Filipino community-based organizations, enrolled into this study, provided with the cookbook, and asked to cook at least one recipe. Pre- and post-intervention surveys were conducted and centered around behavior change and features of the cookbook. This study provided evidence for the cookbook’s acceptability and feasibility, with participants’ open-ended responses revealing that the recipes, nutrition labels, illustrations, and cultural aspects of the cookbook increased motivation to achieve dietary change, including reducing sodium in their diet to improve their blood pressure. Participant responses also indicated positive behavior change as a result of using the cookbook, with participants reporting increased likelihood of adopting recommended actions to lower their BP after utilizing the cookbook (x̅ = 80.83%), compared to before (x̅ = 63.75%, p<0.008), according to Hypertension Self-Care Management scaled scores. In conclusion, the results of this pilot study demonstrated acceptability of this unique cookbook and provide preliminary findings consistent with increased motivation in participants to make dietary changes and improve personal health, drawing attention to the importance of considering future culturally-tailored health interventions. Next steps should include a robust, randomized controlled trial design comparing measured blood pressure outcomes of an intervention vs. control group. *Filipinx is an inclusive term representing the gender identities of all participants in our study